(3GdETQGa Ydi eYQaI GdCWQGas - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3CHh gQjQI Hf GdOHhSi hGNJda ai GSeg GNJdGakG cKjQkG Yf YeQ MOjK deG Jhai QShd Gddg Udi Gddg Ydjg hSde hGSJNda CHh HcQ hcaQ ef caQ ef GdYQH bGd YeQ dCHi HcQ cja JbGJd GdfGS s
(3BNQgG (B:s
(3MOjK ajeG SbJ GdSeG hGdYjhf GdYTQ GdMOjK ai GdRcGI Yf CHj ehSi GdCfUGQi Yf BNQg s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
Keywords: (3GdMOjK h GdeUWdMs